Efeitos do treinamento com exercícios na capacidade funcional e qualidade de vida em indivíduos com insuficiência cardíaca e transplantados cardíacos - Maria do Socorro Quintino Farias (2019)
Cardiovascular diseases (CVD) are the leading causes of death in most countries and Heart Failure (HF) is a growing public health problem with an estimated prevalence of 37.7 million individuals worldwide. HF usually results from structural or functional changes from previous cardiac pathology and its clinical approach includes drug treatment, advanced features such as resynchronizers, artificial ventricles and heart transplantation is recommended for refractory cases. In addition to a clinical treatment, as well as for other heart conditions, heart failure individuals or transplanted recipients should be referred for cardiac rehabilitation (CR). Cardiac Rehabilitation multidisciplinary team provide proper nutrition and psychological counseling, advice on proper medication use, exercise capacity assessment, care counseling while performing physical activities, and often HF patients are engaged in a supervised exercise program at the rehab center. The effects of exercise programs on heart failure individuals and heart transplant recipients have been shown in many studies. However, regarding these groups, there is no consensus about the effects of different protocols of exercise on functional capacity and healthy related quality of life. Continuous or high intensity interval protocols may trigger different responses to heart failure individuals. On the other hand, the literature is scarce and there is still no consensus on whether it is possible to increase functional capacity early after heart transplant surgery. Thus, the objectives of this Thesis were: 1) to evaluate the effects of high intensity interval training protocols in comparison with moderate continuous training protocols on functional capacity, on health-related quality of life and daily living activities of individuals with HF treated exclusively by public health system; 2) to examine the effects of aerobic exercise on functional capacity and health-related quality of life after heart transplantation early after surgery. The first objective was investigated from a blinded, randomized controlled trial, registered at the Rede Brasileira de Ensaios Clínicos (REBEC) (RBR-776gwc) and conducted following the guidelines for nonpharmacological interventions (Consolidated Standards of Reporting Trials CONSORT, 2010). Also, the study was submitted to Plataforma Brasil, and the research ethics approval has been secured from Federal University of Minas Gerais (UFMG), Belo Horizonte - MG, and Hospital de Messejana Dr. Carlos Alberto Studart Gomes, in Fortaleza - CE Brazil (CAAE / 45597115.3.0000.5039). Were considered eligible, all the heart failure Individuals referred to the University Hospital in Belo Horizonte and to the Cardiac Rehabilitation department of the Hospital de Messejana in Fortaleza-CE. Were included optimally treated male or female heart failure patients with reduced-ejection fraction (HFrEF) and intermediate group (HFpEF-borderline) based in an echocardiogram performed at list three months before evaluation. They should also have a maximal exercise stress test or cardiopulmonary exercise test performed within two months before starting the research protocol. Individuals with atrial fibrillation or any other arrhythmia that prevented heart rate control during the study protocol; implantable cardioverter defibrillator (ICD) and fixed frequency pacemaker; physical limitations that prevent participation in the program, as well as those with cognitive impairment, were excluded. The dependent variables were the walking distance (m) in the Incremental Shuttle Walk Test (ISWT) (main), the quality of life assessed by the Minnesota Living with Heart Failure Questionnaire – MLHFQ and the daily activity level assessed by the Duke Activity Status Index – DASI. The independent variables were, left ventricular ejection fraction (LVEF), functional class (NYHA), age, sex, body mass index - BMI (kg/m2), cardiac failure etiology. The outcomes were assessed at before and twelve weeks after training. The individuals were randomly allocated in two groups: the TC Group (Continuous Training) performed a usual training protocol with continuous exercises of moderate intensity, routinely used by the rehabilitation center and the HIIT Group (High Intensity Interval Training) performed the protocol of high intensity interval aerobic exercises. The groups received 12 weeks of supervised training twice/week and the exercise prescription included five minutes of warm-up, thirty minutes of aerobic activity on a treadmill, cycloergometer, mini-trampoline or walking on the ground and five minutes of cooling down. The warmup exercise included light and endurance exercises and could be performed personally or in groups of up to six participants. The intensity of training was programmed individually for each phase of the protocol. The TC Group had the heart rate training zone calculated with heart rate reserve percentages; (HRR = HRmax - HRrest). In the first four weeks, the intensity was calculated between 50 and 60% of the HRR; from the fifth to the eighth week, between 60 and 70% of the RHR and the ninth and twelfth week the intensity was 70 to 80% of the HRR. For the HIIT Group, training was applied in three stages, the short training was applied from first to fourth week: 30 seconds of workouts with intensity of 80% to 90% HRR, followed by 30 seconds of active rest at 30-40% HRR. The intermediate workout from the fifth to eighth week, with two minutes of high intensity between 85 to 95% of the HRR, followed by two minutes of active rest with 40-50% HRR and the extended workout was applied in the last four weeks taking four minutes of high intensity between 90 and 100% of the HRR, followed by three minutes of active rest with 50-60% of the HRR to reach a total of 30 minutes. The groups received recommendations to practice continuous aerobic physical exercise at home (walking or cycling) for 20 to 30 minutes to complete five times per week using the Rating of Perceived Exertion (RPE) Borg Scale to grade the intensity of exercise, that should be moderated. The degree of comfort of the individuals concerning the training program was evaluated using a specific question included in the final evaluation of a five-item Likert scale. The second objective was investigated through a retrospective study, carried out from a database from the CR department of the Hospital de Messejana in Fortaleza CE. The study was registered with the Research Ethics Committee. 95 adult individuals underwent orthotopic heart transplantation between 2015-2018 at the Messejana Hospital. After hospital discharge, the clinically stable transplant recipients taking standard immunosuppressive therapy for rejection control (calcineurin inhibitor, mycophenolate sodium and prednisone) were referred to CR (phase II). Also, endomyocardial biopsy to exclude cardiac allograft rejection were done. Seventy-six individuals were referred to CR and 44 participated in the exercise training program at this period were included in this study. Clinical data (waiting period, age, gender, weight, height, body mass index, HF etiology, and left ventricular ejection fraction (LVEF) were obtained from the patient's medical records and the data regarding the functional capacity and physical training in the Physiotherapy and Rehabilitation Department. Before and after (1-3 weeks) of training, the subjects underwent the Cardiopulmonary Exercise Test (CPET). The aerobic exercise training with continuous of moderate intensity and resistance exercises were applied 86 ± 31 days after transplantation. The data of the six-minute walk tests were recorded, as well as the scores of the healthy quality of life questionnaire and the results of the cardiopulmonary exercise test before and after training. Cardiometabolic variables were analyzed: resting heart rate (HRR), maximum heart rate (HRMAX), anaerobic threshold (LA), anaerobic threshold heart rate (LAHR), oxygen uptake (VO2), metabolic equivalent (R), VE / VCO2 and pulse of oxygen. Before the program, the individuals also performed a six-minute walk test. The training consisted of continuous aerobic exercise sessions three-time/week for four to six months. The 60-minute exercise sessions were applied with 30 minutes of aerobic training on treadmills, bicycles and mini trampoline, and the sessions were monitored Borg Scale between 12 and 13 added 20 minutes of resistance training exercise for large muscle groups using free weight (1-5kg) or weight enough to perform 12-15 times / muscle group without fatigue and the recovery period was five to ten minutes with lower intensity exercise followed by stretching. Systemic blood pressure and heart rate were checked at rest, peak exercise and five minutes before and after the recovery. The Portuguese version of the MLHFQ was also applied. Forty-four individuals were included in this study, representing 56.8% of the total number of transplants referred during the study period. The mean age of 47 ± 12 years old, 80% male were introduced into the program. The comparison between pre and post-training data showed significant improvement (p<0.05) after 16 to 24 weeks of training in walking distance, in walking test, and quality of life, as well as in oxygen consume, in the anaerobic threshold, in the oxygen pulse and in the recovery of heart rate. The analysis showed significant differences after training in physical capacity measured by TCPE (VO2PEAK) 19.62 ± 4.10; 21,46 ± 5,55 and functional capacity (6MWT) 443,2 ± 100,34; 534,6 ± 98,62 meters, as well as improvement in quality of life: MLHFQ 25 (IQ16-45.7; 8 (IQ 3,5-17,5) pre and post physical training respectively. HR in the recovery period in CPET was also lower after training. No significant differences were found in resting HR and peak exercise after training. Both studies indicate positive results of exercise intervention in subjects with heart failure and transplanted in CR programs of the Brazilian public network. In general, the exercises are beneficial for this population observing the safety criteria recommended by the international guidelines.